What makes teachers stay? A cross-sectional exploration of the individual and contextual factors associated with teacher retention in Sweden. (May 2022) - Casely-Hayford, Jeffrey; Björklund, Christina; Bergström, Gunnar; Lindqvist, Per; Kwak, Lydia
Abstract: This cross-sectional study aimed to identify individual and contextual factors associated with Swedish teachers' intention to remain in the profession. A sample of 5903 elementary-year teachers completed a questionnaire between 2004 and 2011 assessing their health and perception of individual and contextual factors at work. The findings showed that teachers' intention to remain in the profession is mainly explained by individual factors, predominantly by teachers' perceived health state, work motivation and collegial support. The main implication is the importance of teachers' perceived health state for their intention to remain, underscoring the importance of a health promoting work environment in schools. Highlights: Teachers' perceived health state is strongly associated with their intention to remain in the profession. Teachers' work motivation is related to their intention to remain in the profession. Social support from colleagues is an important contextual factor influencing teachers' retention intention.